Contact mechanics with maximum-entropy meshfree approximants blended with isogeometric analysis on the boundary. (1st April 2017) - Greco, F.; Rosolen, A.; Coox, L.; Desmet, W.
Highlights: A coupled isogeometric-meshless approach is applied to the simulation of contact. A new strategy is proposed for the numerical integration. Some numerical examples are studied, including a gear contact simulation. Abstract: This paper explores the simulation of small deformation contact problems with a coupled isogeometric-meshless formulation, based on local maximum-entropy (LME) approximants. The framework of isogeometric analysis (IGA) is employed on a thin region close to the boundary of the domain and the meshless formulation in its interior. The method maintains the advantages of IGA in the simulation of contact and introduces a higher flexibility in the discretization of complex shapes. In addition, a new integration strategy is presented for the IGA-LME blending and its advantages respect to the original approach are discussed.